2018
DOI: 10.1002/adfm.201801710
|View full text |Cite
|
Sign up to set email alerts
|

The Drive Force of Electrical Breakdown of Large‐Area Molecular Tunnel Junctions

Abstract: The origin of electrical breakdown of molecular tunnel junctions is systematically studied by determination of the breakdown voltages as a function of six types of bottom-electrodes (Au, Ag, Pt, Pd, Ni, and Cu) and different thickness of self-assembled monolayers of n-alkanethiolates, S(CH 2 ) n-1 CH 3 with n = 2, 4, …, 18, with GaO x /EGaIn top contacts. It is found that at positive bias, the migration of metallic atoms is dominated by the wind force, but, at negative bias, both the wind force and direct forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 85 publications
4
47
0
Order By: Relevance
“…It provides an effective and desirable solution to predicate and control synaptic functions, which is important to backpropagation learning algorithms. 53 However, the EPSC value in the ON state is almost thirty times that in the OFF state with the same amplitude of voltage stimuli, where the ON/OFF states can reversibly switch by a corresponding pulse of V Set (0.8 V) and V Reset (−1.2 V). This means that the synaptic plasticity of the Ag/ HfO x /ITO memristive synapse can be modulated via the resistive states of devices, namely synaptic metaplasticity.…”
Section: Resultsmentioning
confidence: 98%
“…It provides an effective and desirable solution to predicate and control synaptic functions, which is important to backpropagation learning algorithms. 53 However, the EPSC value in the ON state is almost thirty times that in the OFF state with the same amplitude of voltage stimuli, where the ON/OFF states can reversibly switch by a corresponding pulse of V Set (0.8 V) and V Reset (−1.2 V). This means that the synaptic plasticity of the Ag/ HfO x /ITO memristive synapse can be modulated via the resistive states of devices, namely synaptic metaplasticity.…”
Section: Resultsmentioning
confidence: 98%
“…Here, we note that some data points at high temperatures and at large applied bias suffer from noise likely because these conditions approach the breakdown voltage of our devices. [ 31 ] c) E a versus V at positive bias. The solid red line is a fit using the Marcus rates given in Equations ( 5a ) and ( 5b ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported before that the breakdown voltage of tunnel junctions consisting of dissimilar electrodes is not symmetrical due to the intrinsic electric field caused by the difference in the work function of the electrode materials. [66,67] We also found that our devices were not stable at large positive bias; therefore, we limited the bias window in our experiments to −2.0 to 1.0 V to prevent electrical failure. To ensure that coherent tunneling dominates the charge transport mechanism across the Al-AlO X -Cu junctions, we recorded an I(V) before the optical characterization.…”
Section: Electrical and Optical Characterization Of Tunnel Junctionsmentioning
confidence: 96%